2012
DOI: 10.1017/s1755267211001114
|View full text |Cite
|
Sign up to set email alerts
|

First record of the pelagic thresher shark Alopias pelagicus (Pisces: Alopiiformes: Alopiidae) from the Lakshadweep Sea, India

Abstract: The pelagic thresher shark Alopias pelagicus is a large, wide-ranging Indo-Pacific Ocean pelagic shark. In this paper, the first record of the pelagic thresher shark, caught from the Lakshadweep Sea is reported. The shark 275 cm in total length was caught by drift longline operation at depth of 60 m in the Lakshadweep Sea (10852N latitude 72813E longitude).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…However, vertical space use also has important management implications, and predictable vertical movements by silvertip sharks may increase their vulnerability to fishing, but also be used to tailor enforcement activities to periods of greatest risk. The silvertip shark's core depth range in the BIOT MPA overlaps with the relatively shallow (30-100 m depth) longlines set by regional fishing fleets (Aneesh et al 2016, Hewapathirana & Gunawardane 2017, some of whom are known to illegally fish in BIOT (Martin et al 2013. found that silvertip sharks' wider movements around the Chagos Archipelago increased their exposure to illegal fishing activity; predictable vertical space use may increase their vulnerability by allowing fishers to target them based on simple environmental cues.…”
Section: Vertical Space Use Management and Conservationmentioning
confidence: 99%
“…However, vertical space use also has important management implications, and predictable vertical movements by silvertip sharks may increase their vulnerability to fishing, but also be used to tailor enforcement activities to periods of greatest risk. The silvertip shark's core depth range in the BIOT MPA overlaps with the relatively shallow (30-100 m depth) longlines set by regional fishing fleets (Aneesh et al 2016, Hewapathirana & Gunawardane 2017, some of whom are known to illegally fish in BIOT (Martin et al 2013. found that silvertip sharks' wider movements around the Chagos Archipelago increased their exposure to illegal fishing activity; predictable vertical space use may increase their vulnerability by allowing fishers to target them based on simple environmental cues.…”
Section: Vertical Space Use Management and Conservationmentioning
confidence: 99%